Innovation Ecosystem of Switzerland and South Korea - Němečková, Markéta; Hnát, Pavel, 1981-; Kohut, Dominik; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This bachelor’s thesis aims to contribute to a broader understanding of how distinct elements can form successful innovation-focused economies, such as Switzerland and South Korea, by conducting a comparative analysis of the countries' innovation ecosystems. The primary goal is to identify the differences in internal elements (strengths and weaknesses) as well as in the external components (opportunities and threats) shaping countries’ innovation ecosystems. The first part introduces the concept of innovation and innovation policy, along with the roles of ecosystem actors based on Helix models. The second part analyses both countries using relevant indicators across five key subsystems: political, economic, educational, societal, and environmental. Finally, a SWOT analysis highlights the strengths, weaknesses, opportunities, and threats of both ecosystems to provide insights for policymakers and stakeholders.
Vedoucí práce: Pavel Hnát
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses